2019
DOI: 10.3389/fmech.2019.00062
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of CO2 and NOx Emissions of One Diesel and One Bi-Fuel Gasoline/CNG Euro 6 Vehicles During Real-World Driving and Laboratory Testing

Abstract: The objective of this study is the assessment of the real-world environmental performance, and its comparison with laboratory measurements, of two Euro 6 passenger cars. The first is equipped with a common-rail diesel engine, Lean NO x Trap (LNT), and Diesel Particulate Filter (DPF), and the second is a bi-fuel gasoline/CNG (Compressed Natural Gas) vehicle equipped with a Three-Way Catalyst (TWC). The experimental campaign consisted of on-road and chassis dynamometer measurements. In the former test set, two d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(17 citation statements)
references
References 27 publications
(38 reference statements)
2
15
0
Order By: Relevance
“…Gaseous emissions of CNG cars have been studied in some detail (Chen, He, and Zhong 2019;Jahirul et al 2010;Yusaf et al 2010). The emission levels of gaseous pollutants with CNG are generally lower for CO 2 and CO and higher for NO x when compared to gasoline (Dimaratos et al 2019). With regard to particulate emissions, a Euro 6 CNG vehicle in real drive emissions (RDE) testing exhibited, Solid Particle Number (SPN) emissions greater than 23 nm (SPN >23nm ), that were as low as a diesel particle filter (DPF) equipped vehicle (Kontses et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Gaseous emissions of CNG cars have been studied in some detail (Chen, He, and Zhong 2019;Jahirul et al 2010;Yusaf et al 2010). The emission levels of gaseous pollutants with CNG are generally lower for CO 2 and CO and higher for NO x when compared to gasoline (Dimaratos et al 2019). With regard to particulate emissions, a Euro 6 CNG vehicle in real drive emissions (RDE) testing exhibited, Solid Particle Number (SPN) emissions greater than 23 nm (SPN >23nm ), that were as low as a diesel particle filter (DPF) equipped vehicle (Kontses et al 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The authors of the articles [18,26] pointed out the importance of the cold start issue as well as the necessity of further improvement of exhaust after-treatment systems. Whereas, the authors of the publications [8,10,11] suggested that NO x emission should be an issue addressed in subsequent updates of EU regulations. According to the authors of the publication [8], the NO x emissions from vehicles, equipped with a gasoline engine, are increasingly higher and consequently, particularly important in the context of urban air quality.…”
Section: Introductionmentioning
confidence: 99%
“…Whereas, the authors of the publications [8,10,11] suggested that NO x emission should be an issue addressed in subsequent updates of EU regulations. According to the authors of the publication [8], the NO x emissions from vehicles, equipped with a gasoline engine, are increasingly higher and consequently, particularly important in the context of urban air quality. The authors also pay attention to the value of the ambient temperature at which the RDE test is performed.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…There can be some issues connected with the emission of ammonia which contributes to particle pollution [60,61]. It has been also been noted that CNG vehicles can emit more NOx emission comparing to petrol vehicles [62]. The cost of installation of the CNG fueling system to the cars that have not been equipped with this system by the vehicle manufacturer is also very high.…”
Section: Introductionmentioning
confidence: 99%